Applications of stable carbon isotopes in soil science with special attention to natural 13C abundance approach - Zacháry, Dóra (Hungarian Geographical Bulletin, 2019)
Since the invention of the isotope ratio mass spectrometer, isotope analysis has shed light on many key processes in the Earth’s ecosystems. Stable isotope analysis was first applied in the field of chemistry and geochemistry, while the use of isotopic fractionation for various biochemical reactions was elaborated later. The knowledge gained from isotope research led to a better understanding of the dynamics of the biosphere and to the more efficient study of interactions between the geosphere and biosphere. In soil research, stable isotopes are ideally suited to provide a wider insight into the element cycles in soil ecosystems. Stable carbon isotopes, in particular, have been in the focus of soil research, since soil organic matter (SOM) plays an important role not only in soil fertility, soil water management and many other physical, chemical and biological soil functions, but also in the global carbon cycle. If processes connected with these soil functions are isotopically labelled with stable carbon isotopes, the key reactions of C input, exchange and output in the soil and other soil organic matter functions can be studied accurately. Moreover, analysing the isotopic composition of CO2 exchange between the soil and the atmosphere helps to predict ecosystem responses to global changes.